2021
DOI: 10.1016/j.fertnstert.2021.07.283
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Live Birth From Single Euploid Frozen Blastocyst Transfer Using Standardized Timing Versus Timing by Endometrial Receptivity Analysis

Abstract: directed selection (OR 5.78;). There were no differences in PR between groups after first transfer (OR 0.84,.CONCLUSIONS: In our cohort, adjusted for age, there were no differences in the euploidy rates between TB and FB groups. However, PGT-A was associated with improved PR. Moreover, the lack of difference in euploidy rates and PR after TB suggest that TB is not detrimental to clinical outcomes.IMPACT STATEMENT: Our analysis is the largest cohort assessing euploidy and pregnancy rate after TB. While there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Although the timing for embryonic transfer is essential, it is not a limited time interval [ 49 ]. Recently, data from two large trials and a meta-analysis showed no clinical benefits associated with endometrial receptivity analysis of the WOI shift [ 50 , 51 , 52 ]. The nature of the WOI shift in different menstruation cycles may be governed by normal inter-cycle variation instead of pathological changes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the timing for embryonic transfer is essential, it is not a limited time interval [ 49 ]. Recently, data from two large trials and a meta-analysis showed no clinical benefits associated with endometrial receptivity analysis of the WOI shift [ 50 , 51 , 52 ]. The nature of the WOI shift in different menstruation cycles may be governed by normal inter-cycle variation instead of pathological changes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the controversy generated by the aforementioned trial, a recent large randomized, controlled trial of the use of PET for transfer of euploid blastocysts was performed that avoided the heterogeneity of the first trial as well as the high dropout rates and differences between intention to treat and per protocol analyses. The trial was presented at the 2021 meeting of the American Society of Reproductive Medicine [85]. All patients underwent PGT-A and randomization occurred only if patients had at least one euploid blastocyst.…”
Section: Endometrial Receptivity Arraymentioning
confidence: 99%
“…A large, randomized controlled trial demonstrated no benefit of ERA-guided embryo transfer in patients who underwent standard-timing frozen euploid blastocyst transfer over patients who underwent ERA-timed frozen euploid blastocyst transfer (3). The subject of this commentary, the study by Cozzolino et al (4) differed by evaluating patients who had a prior failed embryo transfer and also included donor egg cycles.…”
mentioning
confidence: 99%